Metacognition Development Through Stad Learning Assisted With Module by Using Diagnostic Assessment to Improve The Problem Solving Ability - Setyawan, Arif Budi; Sukestiyarno, Sukestiyarno (Universitas Negeri Semarang, 2018)
This study has purpose to (1) determine the effectiveness of STAD learning assisted with module by using a diagnostic assessment on the ability of mathematical problem solving, (2) describe the problem solving abilities reviewed from metacognition in the learning model of STAD assisted with module by using diagnostic assessment, (3) find out the results of diagnostic assessments follow up of students problem solving ability in the learning model of STAD assisted with modules. The type of this study was mixed method with concurrent embedded design. The subjects of this study were students of grade XI SMA Negeri 1 Weleri. The results obtained from the analysis were (1) STAD learning assisted with module by using diagnostic assessment is effective, (2) it was found on the pattern of problem-solving abilities that (1) students with high metacognition were able to solve problem in accordance to the step proposed by Polya, (2) most of students with moderate metacognition did not recheck the problem solving, (3) students with low metacognition could not perform the problem solving plan and recheck the problem solving, (3) after conducted summative test, obtained average value of 77.65, this result indicated that most of the students obtained higher score than minimum completeness score.